Kearifan Ekologis Masyarakat Pasemah dalam Legenda: Kajian Ekokritik Sastra Lisan - Bunga Satria Diani; Bustanuddin Lubis; Yayah Chanafiah; Febi Junaidi (CV. Era Digital Nusantara, 2026)
This study aims to describe the ecological values and the relationship between the legends of the Pasemah ethnic community and the environmental ecosystem in Kedurang and Kedurang Ilir Districts, South Bengkulu Regency. The study employs a qualitative approach using a descriptive method. The research data consist of six legends collected through interviews, documentation, and audio recordings obtained from informants. Data were analyzed by examining the ecological values and environmental ethics reflected in the legends. The findings reveal that these legends embody five environmental ethics: respect for nature, responsibility, solidarity, care and compassion, and non-interference with natural life. The legends also demonstrate a close relationship with the environmental ecosystem, portraying nature as an essential part of community life and as a medium for fostering ecological awareness. Therefore, the legends of the Pasemah ethnic community in South Bengkulu Regency serve as one of the traditional ways through which earlier generations instilled ecological awareness in their descendants. These values function as guidelines for life, encouraging people not to exploit or damage nature but rather to maintain balance and harmony between humans and the environment.